Critical Investigation on the Pandemic from the Islamic Perspective - Ramli, Ahmad Faizuddin; Ramli, Nusairah; Huda, Miftachul; Hussain, Liya Khaulah Asy-Syaimaa’; Ramli, Nur Isti’anah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
Since the emergence of the global challenges of COVID-19 pandemic, its impact could be widely viewed in various human society aspects, such as education, business trading and also social interaction limit. Apart from many discussions on the pandemic from a wide range of such perspectives, scholarly attention is still rarely mainly in trying to elaborate the critical overview from an Islamic perspective following theological, historical, and sociological points of view. In this paper, the critical elaboration of the pandemic has been widely discussed by analysing the contents of sacred scriptures and responses from an Islamic point of view. The literature was critically conducted from religious sources such as the Qur’an and Hadith, and also related contemporary works. The finding reveals that the pandemic has been given full attention as stated in the Qur’an and narrated in Hadith by taking a lesson from pandemics and strategically battling the pandemic. The following attentions were addressed in order to strengthen the Muslim community and society in order to support the health protocols arranged by the local and international health organizations. The value is that religion’s clear comprehension could give continued support to encourage the Muslim community especially and general society at large in the attempts to battle the spreading pandemic.